Trends in blood sugar, glycated hemoglobin, lipid profile, Vitamin B12, and Vitamin D in Alavi Bohra women – A micro minority Muslim community cohort study (Journal of Food and Dietetics Research, 2023)
Background and Aim: Community cohort studies play an essential role in gaining knowledge about diseases and reducing their associated burden in women. The present study aimed to assess the trends of blood sugar, glycated hemoglobin, lipid profile, Vitamin B12, and Vitamin D in women of reproductive age from varying socioeconomic status from the micro minority Muslim Alavi Bohra community residing in Vadodara city.Materials and Methods: A cross-sectional community cohort study wherein all women of the Alavi Bohra community from Vadodara city (19-45 years) (n=95), were purposively selected (IECHR/FCSc/PhD/2021/124). Data were elicited on socio-economic status (SES) and biochemical profile. Fasting blood sugar, glycated hemoglobin, vitamin B12, and vitamin D) using standard protocols and data were segregated based on two classes of socioeconomic status (Lower SES and Upper SES) as per the modified Kuppuswamy socio-economic scale (2021) and analyzed using JASP software for statistical analysis.Result and Discussion: The Alavi Bohra are immigrants from Egypt and Yemen and follow a distinct Muslim culture and lifestyle. The mean age of the women was 33 years (range 21-42 years), and the average income was Rs. 20669 vs Rs. 77162 for low and high-income groups respectively. Biochemical indices revealed that 83% of women had prediabetes as per International Diabetes Federation guidelines (2015), mean FBS of 117 mg/dl with mean HbA1c of 5.7 and vitamin D of 14.36 ng/ml, and mean vitamin B12 of 489.62 pg/ml, and mean total cholesterol of 166 mg/dl, however, women of both groups suffered from metabolic imbalances.Conclusion: There was no significant difference between the lower and upper socioeconomic groups of women. However, a high risk of diabetes, dyslipidemia, and vitamin D deficiency was reported irrespective of socioeconomic class. An in-depth study of their culture and, dietary habits along with social and behaviour change communication is needed for improving the health of women.
Keywords: Alavi Bohra; Prediabetes; Diabetes; Food Anthropology; women's Health; Socioeconomic status; community cohort study